Ethical and Effective Policy Development for Implementing Random Drug Testing Within Higher Education Institutional Frameworks - Mary Rose F. Montano; Ronald A. Gonzales; Regina G. Almonte; Elvinard R. Reyes; Nilo O. Armario Jr.; Anna Rhea C. Opeña; Eldie R. Bermudo Jr. (Research Synergy Foundation Press, 2026)
Drug use among youth remains a pressing concern throughout the Philippines, carrying significant implications for student welfare and campus safety. Consequently, the City College of Calamba (CCC) is considering implementing random drug testing to comply with Republic Act No. 9165, the Comprehensive Dangerous Drugs Act of 2002. However, the ethical and practical challenges of such programs necessitate careful development to balance safety with respect for privacy, dignity, and trust. This study was designed to investigate stakeholder perceptions, concerns, and recommendations regarding the ethical implementation of random drug testing. A qualitative case study design was employed, using open-ended surveys distributed to 42 CCC stakeholders, including students, faculty, and staff, purposively selected for their roles and institutional involvement. Thematic analysis successfully identified several key patterns, with themes validated through reliability checks. Stakeholders recognized potential benefits, such as enhanced safety and deterrence, yet prominent concerns regarding privacy, confidentiality, emotional impact, and fairness emerged. Participants stressed the importance of ethical safeguards, transparency, and a rehabilitative rather than punitive approach. The proposed policy framework prioritizes informed consent, impartial selection, strict confidentiality, and support services. By focusing on information-rich participants, this study contributes to a vital stakeholder-informed policy framework for higher education. It addresses gaps in ethical implementation and aligns with national laws, offering practical insights for institutions seeking to balance safety with student rights. Ultimately, this research fosters trust and cooperation within the academic community, ensuring institutional values and legal mandates are carefully integrated to promote a secure, supportive, and drug-free environment.